Capital Controls, Political Risk, and Deviations from Interest-Rate Parity - Dooley, Michael P.; Isard, Peter (Journal of Political Economy, 1980)
It is shown that the interest differential due to political risk, given the prospect of future capital controls, depends essentially on the gross stocks of debt outstanding against different governments and the distribution of world wealth among residents of different political jurisdictions. A simple model of portfolio behavior is used to explain the differential between Euromark rates and interest rates within Germany in the presence of controls on capital flows into Germany between 1970 and 1974. The explanation separates the interest differential into the effective tax imposed by existing controls and a political risk premium associated with prospective controls.